Pengaruh Citra Merek dan Kepercayaan Merek terhadap Loyalitas Merek Mie Instan - Armanto, Rully; Islamiah, Bella; Gunarto, Muji (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
The purpose of this study was to determine the effect of brand image and brand trust on brand loyalty. The population in this study were students in the city of Palembang. The sampling technique used Accidental Sampling and obtained a research sample of 400 respondents. The variables of this study used two variables, namely the dependent and independent variables. Data analysis using multiple linear regression analysis model with SPSS program. The results showed that partially or simultaneously the variable brand image and brand trust had a significant effect on brand loyalty, for the variable that had the most dominant influence was brand image. There are several implications including the impact of instant noodles that are not good for health and the reputation of instant noodle products that are not guaranteed.